Characterization of Terbium and Samarium Co-Doped Ceria Films Prepared Using Ultrasonic Spray Pyrolysis. Issue 8 (1st January 2015) - Vestli, Mihkel; Lust, Enn; Nurk, Gunnar
Abstract : Tb and Sm cation binary co-doped ceria films were deposited using the ultrasonic atomizing spray pyrolysis method. Crack-free homogenous films with different dopant concentrations were deposited and thereafter annealed at fixed temperatures T = 900, 1200 and 1300°C, respectively. It was demonstrated that several microstructural parameters of oxide films are controlled by the sintering temperature. The Ce0.9 Sm0.1-x Tbx O2-δ films formed were analyzed using X-ray diffraction, scanning electron microscopy, high resolution transmission electron microscopy, atomic force microscopy and a four probe DC technique at different pO2 and temperature conditions. Based on the SEM analysis the average thickness of the Ce0.9 Sm0.1-x Tbx O2-δ films was approximately 700 nm. The XRD patterns for the Ce0.9 Sm0.1-x Tbx O2-δ films annealed at 1200°C indicated a high degree of crystallinity. Tb dopant ions influence the microstructural properties like median diameter of grains, microstrain, lattice parameter and electrical properties like activation energies of ionic and electronic part of conductivity for the Ce0.9 Sm0.1-x Tbx O2-δ film. A significantly higher microstrain value for the lowest Tb dopant concentration with accompanied change in electrical properties was observed.